Molecular phylogeny of the highly diversified catfish subfamily Loricariinae (Siluriformes, Loricariidae) reveals incongruences with morphological classification - Covain, Raphaël; Fisch-Muller, Sonia; Oliveira, Claudio [UNESP]; Mol, Jan H.; Montoya-Burgos, Juan I.; Dray, Stéphane (Elsevier B. V., 2015)
The Loricariinae belong to the Neotropical mailed catfish family Loricariidae, the most species-rich catfish family. Among loricariids, members of the Loricariinae are united by a long and flattened caudal peduncle and the absence of an adipose fin. Despite numerous studies of the Loricariidae, there is no comprehensive phylogeny of this morphologically highly diversified subfamily. To fill this gap, we present a molecular phylogeny of this group, including 350 representatives, based on the analysis of mitochondrial and nuclear genes (8426 positions). The resulting phylogeny indicates that Loricariinae are distributed into two sister tribes: Harttiini and Loricariini. The Harttiini tribe, as classically defined, constitutes a paraphyletic assemblage and is here restricted to the three genera Harttia, Cteniloricaria, and Harttiella. Two subtribes are distinguished within Loricariini: Farlowellina and Loricariina. Within Farlowellina, the nominal genus formed a paraphyletic group, as did Sturisoma and Sturisomatichthys. Within Loricariina, Loricaria, Crossoloricaria, and Apistoloricaria are also paraphyletic. To solve these issues, and given the lack of clear morphological diagnostic features, we propose here to synonymize several genera (Quiritixys with Harttia; East Andean members of Crossoloricaria, and Apistoloricaria with Rhadinoloricaria; Ixinandria, Hemiloricaria, Fonchiiichthys, and Leliella with Rineloricaria), to restrict others (Crossoloricaria, and Sturisomatichthys to the West Andean members, and Sturisoma to the East Andean species), and to revalidate the genus Proloricaria.
Keywords: Amazon basin; Freshwaters; Mitochondrial genes; Neotropics; Nuclear genes; Systematics